THE EFFECTIVENESS OF GROUNDWATER TAX SERVICES IN ENHANCING REGIONAL ORIGINAL REVENUE: A POLICY IMPLEMENTATION ANALYSIS IN LOCAL GOVERNMENT - Harahap, Afrodita Arika Arnisya; Adam, Adam; Batubara, Beby Masitho (Pena Cendekia Insani, 2026)
This study examines the effectiveness of groundwater tax (Pajak Air Tanah) services as a source of Regional Original Revenue (Pendapatan Asli Daerah/PAD) in Medan City by adopting a public service effectiveness perspective. Unlike previous studies that primarily emphasize fiscal performance, this research applies Steers’ organizational effectiveness framework, which includes goal attainment, integration, and adaptation, to provide a multidimensional analysis of tax service performance. A descriptive qualitative approach was employed to capture institutional practices, service processes, and stakeholder perspectives that cannot be adequately explained through quantitative indicators alone. Data were collected through interviews, observations, and document analysis involving officials of the Regional Revenue Agency (Bapenda) of Medan City. The findings reveal that groundwater tax services have been administratively implemented in accordance with existing regulations, particularly in terms of registration, assessment, and collection procedures. However, the contribution of groundwater tax to PAD remains relatively low due to structural limitations, including a restricted tax base, regulatory policies aimed at controlling groundwater extraction, and the transition toward piped water consumption. From the perspective of goal attainment, service outputs are achieved, yet fiscal targets are only partially fulfilled. In terms of integration, limited communication and weak inter-agency coordination hinder the expansion of the tax base and reduce data accuracy. Meanwhile, adaptation capacity remains reactive, constrained by limited resources and the absence of systematic innovation in service delivery. The study concludes that groundwater tax should not be evaluated solely as a revenue-generating instrument but also as a regulatory tool for environmental governance. Therefore, improving service effectiveness requires strengthening institutional coordination, enhancing data integration systems, and developing adaptive service strategies to balance fiscal objectives with sustainable resource management.